Long-chain and very long-chain ceramide levels in subjects with impaired glucose regulation. - Dimova, Rumyana; Lozanova, Vesela; Chakarova, Nevena; Serdarova, Mina; Kirilov, Georgi; Lozanov, Valentin; Del Prato, Stefano; Tankova, Tsvetalina (Journal of Clinical Lipidology, 2025)
• Ceramide levels and ratios seems to be similar in subjects with 1 hour-OGTT and IGT. • C16:C24 and C18:C24 ratios appear to be lower in insulin resistance. • C16:0 ceramide is independently related to stimulated insulinemia, highlighting the leading role of some specific ceramide subspecies rather than total ceramide levels in the development of insulin resistance and beta-cell dysfunction. • The present study confirms the independent relationship between C16 and C18 ceramides and kidney function in early stages of glucose intolerance. The aim of this study was to determine the ceramide subspecies profile in people with impaired 1-hour or 2-hour postload glucose during a 75 g oral glucose tolerance test (OGTT) and their association with cardiometabolic parameters. Out of 90 subjects (age 46.7 ± 10.5 years; body mass index of 32.0 ± 6.3 kg/m2) who underwent a 2-hour OGTT, 19 had normal glucose tolerance, 22 had 1-hour plasma glucose ≥8.6 mmol/L (1hrOGTT), and 49 had 2-hour >8.6 and ≤10 mmol/L (impaired glucose tolerance). Homeostatic model assessment of insulin resistance (HOMA-IR) was determined for each group and was subdivided into 2 subgroups (HOMA-IR <2.5 or ≥2.5). Areas under the curve (AUCs) for glucose, insulin, C-peptide, and triglycerides were calculated during the OGTT. Ceramides were assessed by liquid chromatography-mass spectrometry on a fasting blood sample. There was no significant difference across the glucose tolerance groups, as well as the subgroups depending on HOMA-IR, for all evaluated lipid markers and ratios. The AUC C-peptide was positively associated with C16 (r = 0.21, P =.051), while a negative relationship was apparent between the insulin secretion-sensitivity index-2 and C24 (r = -0.21, P =.051), HOMA-IR ≥2.5 and the C16/24 (r = -0.22, P =.034), C18/24 (r = -0.22, P =.037), and C24:1/C24 (r = -0.24, P =.022) ratios. Our results demonstrate diminished C16/C24 and C18/C24 ratios in subjects with insulin resistance, and an independent relationship between C16:0 ceramide and stimulated insulinemia, and between C16 and C18 and kidney function, highlighting the leading role of specific ceramide subspecies rather than the overall ceramide levels for the cardiometabolic profile in early stages of glucose intolerance.